How does death harm the person who dies? - Bzdok, Andrew John, author; McShane, Katie, advisor; Cafaro, Philip, committee member; Canetto, Silvia, committee member (Colorado State University. Libraries, 2012)
The objective of this thesis is to identify the most persuasive justification for the common intuition that death is a harm for the person who dies. This goal is achieved by examining the Deprivation Theory and the Desire Thwarting Theory, which are the two most popular theories that explain how and why death harms the person who dies, and identifying what one must theoretically accept to make each theory tenable. The Desire Thwarting Theory claims that death harms the person who dies when it frustrates certain forward-looking desires, and the Deprivation Theory states that death harms the person who dies when death deprives an individual of certain goods she would have received had she not died. I argue that although the Deprivation Theory provides the most persuasive justification for the intuition that death harms the person who dies, it still requires a number of contestable theoretical commitments to make it defensible. I conclude that the Deprivation Theory provides a convincing justification for the common intuition that death is a harm for the person who dies only if one accepts the following claims: (a) that death can result in a genuine loss of future goods for the person who dies, (b) that the fact that the theory cannot provide a single evaluation of whether death is a harm for the person who dies isn't a problem for the theory, and (c) that we can either identify the time when the person who dies is worse off as a result of her death or defend the claim that the harm of death is a timeless harm.
Keywords: Epicurus; Bzdok; death; harm; McMahan; philosophy